Hubungan konsumsi sugar sweetened beverages dan aktivitas fisik dengan rasio lingkar pinggang panggul siswa MAS Plus Al-Ulum Medan - Sihombing, Hafifah Danea Rosa; Koka, Ecia Meilonna; Lubis, Zulhaida; Ardiani, Fitri (Talenta Publisher, 2024)
The waist-hip ratio (WHR) is the comparison between an individual's waist circumference and hip circumference. This ratio is frequently used in health research to assess body fat distribution and can indicate health risks associated with obesity. This study aims to evaluate the relationship between the consumption of sugar-sweetened beverages and physical activity with the waist-hip ratio among students of MAS Plus Al-Ulum Medan. This research employs a quantitative method with a cross-sectional approach. The results indicate that most students consume excessive amounts of sugar (â‰¥50 grams/day) and have low levels of physical activity. Bivariate analysis using Spearman's rank correlation showed a significant relationship between the consumption of sugar-sweetened beverages and WHR, with a strong and positive correlation. Additionally, there is a significant relationship between the level of physical activity and WHR, with a strong and inverse correlation. Students of MAS Plus Al-Ulum Medan are encouraged to reduce their consumption of sugar-sweetened beverages and increase their physical activity. Keywords: SSBâ€™s, physical activity, WHR, adolescents